Feasibility of Solar Thermal and Photovoltaic Integrated With Building Facade, a Case Study in Thimphu - Subba, Aita Bahadur; Lhendup, Tshewang; Chettri, Roshan; Dorji, Cheku (Bhutan Journal of Research and Development, 2023)
Based on energy simulations, the annual energy demand of the DHI office is estimated to be 3,739 kWh. The total energy includes heating, lighting, and equipment energy requirements. The thermal energy demand of the office is 2,240 kWh and the combined lighting and equipment energy is 1,499 kWh. A radiation analysis of the front of the office is carried out to determine which facade received the most solar radiation. The annual global solar radiation received on building facade are 2.6 kWh/m^2, 2.4 kWh/m^2 and 2.3 kWh/m^2 on south, west and east facing facade respectively. Accordingly, the radiation results concluded that the south-facing facade is the most promising facade, followed by the west-facing facade and the east-facing facade. The proposed STC system, designed to maintain hot water temperature of 55°C, and simulations indicate that it would generate 2,440 kilowatt-hours of heating energy per year. This thermal energy would be sufficient to meet the space heating energy needs of the DHI office. Finally, the possibility of installing photovoltaic (PV) panels on the west-facing facade area 26 m^2 was simulated, suggesting the potential of 2,016 kWh of energy, which could replace the total lighting loads of 1,499 kWh currently received from grid supply.